Blessing of the Ocean Ceremony - Coastal Alliance; Ramirez, Carmen (Coastal Alliance)
Two documents. First: Pamphlet to the community of Ventura County invited to the "Blessing of the Ocean" ceremony to stop threats to the ocean such as LNG from docking and existing problem of the Halaco Plant at Ormond Beach conducted by the Coastal Alliance. Second: Research paper titled "Blessed Salt" by Rev. John H. Hampsch. Takes a look at the religious and spiritual importance of salt throughout history.